Photoacoustic Imaging Principles, Advances and Applications - Gharieb, Reda R. (IntechOpen, 2020)
Photoacoustic imaging (PAI) is an emerging non-invasive imaging modality that integrates the advantages of deep ultrasound penetration and high optical contrast. It provides better resolution than pure ultrasonic imaging and deeper penetration than pure optical imaging. Hence, it is opening new frontiers in diagnostic imaging. Photoacoustic Imaging - Principles, Advances and Applications, provides interested readers with the principle knowledge, advanced methodologies, and new applications associated with PAI technology. Written by expert researchers, chapters cover such topics as the generation and detection of photoacoustic signals, sound source localization, image reconstruction and formation, and application of PAI in gastroenterology and ophthalmology.